A long battle ahead: Malaysian and Singaporean Prime Ministers employ war metaphors for COVID-19 - Kumaran Rajandran (Penerbit Universiti Kebangsaan Malaysia, 2020)
The short article reports a preliminary exploration about how the Prime Ministers of Malaysia and Singapore frame COVID-19 through metaphors. The framing can shape our understanding of the virus. The Prime Ministers gave public broadcasts on or to the media in March, April and May 2020. The analysis of the broadcasts is comprised of metaphor identification using the Metaphor Identification Procedure (MIP), and metaphor interpretation. COVID-19 in the Prime Ministers’ broadcasts is conceptualized by a few metaphors. The Prime Ministers utilize similar metaphors about the virus because metaphors of direction, journey, liquid and war are noted. COVID-19 IS WAR is selected because war metaphors have been recognized for other diseases and they have been commonly deployed during this pandemic. War metaphors frame several aspects of the virus, which cover its description, impact on multiple areas, the actors involved and their reactions. The war scenario can evoke a sense of alarm regarding the threat and severity of COVID-19.